Age of death - Sullivan, Michael J., 1961- (Sullivan, Michael J., 1961- Legends of the First Empire, 2020)
Winter blankets the land, and more than hope has died. Barred by the tower of Avempartha, the western army cannot invade the Fhrey homeland. So it must seek a way across the Nidwalden River before the fane obtains the secret of dragons. As time runs out for both humanity and the mystic Suri, the only chance for the living rests with the dead. Having made their fateful choice, can a handful of misfits do the impossible, or are they forever lost to an inescapable grave? As in Virgil's Aeneid, Dante's Divine Comedy, and Milton's Paradise Lost, the most epic tales transcend the world of the living. It's time to see what lies in Elan's Age of Death.